Non-Decalcified Barium Sulfate-Adsorbed Plasma A Potentially Useful Reagent for Studying Blood Clotting, Platelets or Complement - Zucker, Marjorie B; Owen, John (Thrombosis and Haemostasis, 1982)
Plasma was prepared by rapid centrifugation of native blood followed by adsorption of vitamin K-dependent clotting factors with BaSO4. Compared to fresh citrated plasma, BaSO4-treated plasma contained about 80% of factor V and factor VIII and the same concentration of fibrinopeptide A. Assays were also carried out after overnight incubation of citrated plasma and BaSO4-adsorbed plasma with and without added citrate and compared to assays of fresh citrated plasma. Factor V decreased to about 25% in both citrated samples, factor VIII decreased to 45% in both samples of BaSO4-treated plasma, and fibrinopeptide A did not change. Thus loss of factor V activity depended on reduction in divalent cation concentration whereas loss of factor VIII activity may have resulted from effects of early traces of thrombin.
Keywords: Barium sulfate-adsorbed plasma; Non-decalcified plasma; Factor V; Factor VIII